Psychometric evaluation of the Bengali brief pain inventory in a sample of Bangladeshi cancer patients (Dhaka University Journal of Biological Sciences, 2024)
Pain is a common complain among oncology patients, and success of its management requires accurate assessment. However, the status of pain treatment in Bangladesh is largely undocumented. The purpose of this study was to evaluate the psychometric properties of the Bengali version of Brief Pain Inventory (BPI-Bengali) in a Bangladeshi sample of cancer patients. BPI-Bengali and the Questionnaire on Stress in Cancer Patients Revised (QSC-R 23) were administered to a convenience sample of 60 adult oncology patients receiving pain treatment. Cronbach alpha coefficients were 0.89 and 0.94 for the severity and interference items respectively. The Pearson correlation coefficients for the test-retest stability were 0.65 (p